Etiological structure of neuroinfections - M. V. Nikolskaya; V. L. Melnikov; D. Yu. Kurmayeva; E. A. Vorobyeva; A. V. Afonin; L. N. Aftaeva (Сибирский научный медицинский журнал, 2021)
The aim of the study was to study the etiological structure and epidemiological features of infectious diseases that occur with central nervous system damage in hospitalized patients.Material and methods. A retrospective study of the medical histories of 376 patients with meningitis and encephalitis was conducted.Results and discussion. At the pre-hospital stage, only 198 (52.6 %) patients were diagnosed with «meningitis, encephalitis», which indicates that primary care physicians are not sufficiently alert to diseases of the central nervous system (CNS). When studying the epidemiological history, contact with infectious patients was noted in 69 (18.3 %) patients. The structure of neuroinfections in hospitalized patients was dominated by meningitis (334 cases - 88.8 %), encephalitis was found in 42 (11.2 %) patients. Among meningitis, purulent processes (205 people - 61.4 %) prevailed over serous ones (127 patients - 38.0 %); 2 patients were diagnosed with mycotic meningitis. In adults, the etiology of the disease was clarified in 58 (44.6 %) of 130 patients with bacterial meningitis and in 22 (27.8 %) of 79 with serous meningitis; among children - in 60 (80 %) of 75 patients with purulent meningitis and in 23 (47.9 %) of 48 with serous processes. Encephalitis and meningoencephalitis were detected in 30 adult patients and 12 children. The etiology of encephalitis was established in 13 (43.35) adults and 4 (25 %) children.